Dexmedetomidine Exerts an Anti-inflammatory Effect via α2 Adrenoceptors to Prevent Lipopolysaccharide-induced Cognitive Decline in Mice. (August 2020) - Li, Rong; Lai, Ieng K.; Pan, Jonathan Z.; Zhang, Pengbo; Maze, Mervyn
Abstract : Background: Clinical studies have shown that dexmedetomidine ameliorates cognitive decline in both the postoperative and critical care settings. This study determined the mechanism(s) for the benefit provided by dexmedetomidine in a medical illness in mice induced by lipopolysaccharide. Methods: Cognitive decline, peripheral and hippocampal inflammation, blood–brain barrier permeability, and inflammation resolution were assessed in male mice. Dexmedetomidine was administered in the presence of lipopolysaccharide and in combination with blockers. Cultured macrophages (RAW 264.7; BV-2) were exposed to lipopolysaccharide ± dexmedetomidine ± yohimbine; tumor necrosis factor α release into the medium and monocyte NFκB activity was determined. Results: In vivo, lipopolysaccharide-induced cognitive decline and inflammation (mean ± SD) were reversed by dexmedetomidine (freezing time, 55.68 ± 12.31 vs . 35.40 ± 17.66%, P = 0.0286, n = 14; plasma interleukin [IL]-1β: 30.53 ± 9.53 vs . 75.68 ± 11.04 pg/ml, P < 0.0001; hippocampal IL-1β: 3.66 ± 1.88 vs . 28.73 ± 5.20 pg/mg, P < 0.0001; n = 8), which was prevented by α2 adrenoceptor antagonists. Similar results were found in 12-month-old mice. Lipopolysaccharide also increased blood–brain barrier leakage, inflammation-resolution orchestrator, and proresolving and proinflammatory mediators; each lipopolysaccharide effect was attenuated by dexmedetomidine, and yohimbine prevented dexmedetomidine's attenuating effect. In vitro, lipopolysaccharide-induced tumor necrosis factor α release (RAW 264.7: 6, 308.00 ± 213.60 vs . 7, 767.00 ± 358.10 pg/ml, P < 0.0001; BV-2: 1, 075.00 ± 40.41 vs . 1, 280.00 ± 100.30 pg/ml, P = 0.0003) and NFκB–p65 activity (nuclear translocation [RAW 264.7: 1.23 ± 0.31 vs . 2.36 ± 0.23, P = 0.0031; BV-2: 1.08 ± 0.26 vs . 1.78 ± 0.14, P = 0.0116]; phosphorylation [RAW 264.7: 1.22 ± 0.40 vs . 1.94 ± 0.23, P = 0.0493; BV-2: 1.04 ± 0.36 vs . 2.04 ± 0.17, P = 0.0025]) were reversed by dexmedetomidine, which was prevented by yohimbine. Conclusions: Preclinical studies suggest that the cognitive benefit provided by dexmedetomidine in mice administered lipopolysaccharide is mediated through α2 adrenoceptor–mediated anti-inflammatory pathways. Abstract : Administration of dexmedetomidine to mice treated with lipopolysaccharide decreased neuroinflammation and cognitive impairment in both young and aged mice. The effects of dexmedetomidine on neuroinflammation and cognitive impairment in mice treated with lipopolysaccharide are likely mediated by <2 adrenoceptor–mediated anti-inflammatory pathways.